The Impact of Web-Based Feedback on Physical Activity and Cardiovascular Health of Nurses Working in a Cardiovascular Setting: A Randomized Trial - Reed, Jennifer L.; Cole, Christie A.; Ziss, Madeleine C.; Tulloch, Heather E.; Brunet, Jennifer; Sherrard, Heather; Reid, Robert D.; Pipe, Andrew L. (Frontiers in Physiology, 2018)
A disconcerting proportion of Canadian nurses are physically inactive and report poor cardiovascular health. Web-based interventions incorporating feedback and group features may represent opportune, convenient methods for encouraging physical activity in order to improve levels of physical activity (PA) and the cardiovascular health of nurses. The purpose of this parallel-group randomized trial was to examine the impact of a web-based intervention, which provided participants with feedback from an activity monitor coupled with a web-based individual, friend or team PA challenge, on the PA and cardiovascular health of nurses working in a cardiovascular setting. Methods: Nurses were randomly assigned in a 1:1:1 ratio to one of the following intervention ‘challenge’ groups: (1) individual, (2) friend or (3) team. Nurses wore a Tractivity® activity monitor throughout a baseline week and 6-week intervention. Height, body mass, body fat percentage, waist circumference, resting blood pressure (BP) and heart rate were assessed, and body mass index (BMI) was calculated, during baseline and within 1 week post-intervention. Data were analyzed using descriptive statistics and general linear model procedures for repeated measures. Results: 76 nurses (97% female; age: 46±11 years) participated. Weekly moderate-to-vigorous intensity PA (MVPA) changed over time (F=4.022, df=4.827, p=0.002, ƞ2 =0.055), and was greater during intervention week 2 when compared to intervention week 6 (p=0.011). Daily steps changed over time (F=7.668, df=3.910, p<0.001, ƞ2 =0.100), and were greater during baseline and intervention weeks 1, 2, 3 and 5 when compared to intervention week 6 (p<0.05). No differences in weekly MVPA or daily steps were observed between groups (p>0.05). No changes in body mass, BMI or waist circumference were observed within or between groups (p>0.05). Decreases in body fat percentage (-0.8±4.8 %, p=0.015) and resting systolic BP (-2.6±8.8 mmHg, p=0.019) were observed within groups, but not between groups (p>0.05). Conclusions: A web-based intervention providing feedback and a PA challenge initially impacted the PA, body fat percentage and resting systolic BP of nurses working in a cardiovascular setting, though increases in PA were short-lived. The nature of the PA challenge did not differentially impact outcomes. Alternative innovative strategies to improve and sustain nurses’ PA should be